PENGARUH PENGETAHUAN DAN MOTIVASI TERHADAP SIKAP REMAJA PUTRI YANG MELAKUKAN PEMERIKSAAN PAYUDARA SENDIRI (SADARI) SEBAGAI UPAYA DETEKSI DINI KANKER PAYUDARA DI SMA NEGERI 1 MARBAU KABUPATEN LABUHANBATU UTARA TAHUN 2014 - Rosiah Hasibuan; Heru Santosa; Yusniwarti Yusad (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
AbstractBreast cancer is a malignant tumor which grows in the breast tissue. Nowadays, many patients were found suffered breast cancer at an early age even in fourteen years old has suffered this disease. One of the early detection methods of breast cancer is breast self-examination (BSE). BSE is the most effective and efficient way to find breast cancer at an early stage.This study is aimed to examine the effect of knowledge and motivation to the attitude of girls who do breast self-examination (BSE) as an efforet early detection of breast cancer in SMA 1 Marbau of Labuhanbatu Utara district. The populations in this study were all girls who do the BSE in SMA 1 Marbau with a total sample of 122 respondents. The analysis was used is path analysisThe results showed that the normality test of data, all data were normal distribution and conformance test which used Amos software resulted Goodness of Fit models which fulfill the criteria of fit model. In the hypothesis test resulted that the knowledge obtained significantly influence to the motivations of girls who do BSE with probability value 0,012<0,05 and the motivations significantly influence the attitudes of girls who do BSE with probability value 0,002<0,05 as well as a significant influent between the knowledge toward the girls’ attitudes who do BSE with probability value 0,002<0,05. Furthermore, the results showed that there was the influence of knowledge on the girls’ attitudes through girls’ motivations who do BSE in SMA Negeri 1 Marbau.As a suggestion to reader, the researcher recommend to the school to collaborate with the public health center that would organize counseling activities of the BSE to students so that they can do BSE routinely and regularly.Keywords: Knowledge, Motivation, Attitude, Breast self-examination (BSE), Early detection of Breast cancer